Natural Killer Cells Generated From Human Induced Pluripotent Stem Cells Mature to CD56brightCD16+NKp80+/-In-Vitro and Express KIR2DL2/DL3 and KIR3DL1 - Euchner, Johanna; Sprissler, Jasmin; Cathomen, Toni; Fürst, Daniel; Schrezenmeier, Hubert; Debatin, Klaus-Michael; Schwarz, Klaus; Felgentreff, Kerstin (Frontiers in Immunology, 2021)
The differentiation of human induced pluripotent stem cells (hiPSCs) into T and natural killer (NK) lymphocytes opens novel possibilities for developmental studies of immune cells and in-vitro generation of cell therapy products. In particular, iPSC-derived NK cells gained interest in adoptive anti-cancer immunotherapies, since they enable generation of homogenous populations of NK cells with and without genetic engineering that can be grown at clinical scale. However, the phenotype of in-vitro generated NK cells is not well characterized. NK cells derive in the bone marrow and mature in secondary lymphoid tissues through distinct stages from CD56brightCD16- to CD56dimCD16+ NK cells that represents the most abandoned population in peripheral blood. In this study, we efficiently generated CD56+CD16+CD3- NK lymphocytes from hiPSC and characterized NK-cell development by surface expression of NK-lineage markers. Hematopoietic priming of hiPSC resulted in 31.9% to 57.4% CD34+CD45+ hematopoietic progenitor cells (HPC) that did not require enrichment for NK lymphocyte propagation. HPC were further differentiated into NK cells on OP9-DL1 feeder cells resulting in high purity of CD56brightCD16- and CD56brightCD16+ NK cells. The output of generated NK cells increased up to 40% when OP9-DL1 feeder cells were inactivated with mitomycine C. CD7 expression could be detected from the first week of differentiation indicating priming towards the lymphoid lineage. CD56brightCD16-/+ NK cells expressed high levels of DNAM-1, CD69, natural killer cell receptors NKG2A and NKG2D, and natural cytotoxicity receptors NKp46, NKp44, NKp30. Expression of NKp80 on 40% of NK cells, and a perforin+ and granzyme B+ phenotype confirmed differentiation up to stage 4b. Killer cell immunoglobulin-like receptor KIR2DL2/DL3 and KIR3DL1 were found on up to 3 and 10% of mature NK cells, respectively. NK cells were functional in terms of cytotoxicity, degranulation and antibody-dependent cell-mediated cytotoxicity.